(untitled) (International Journal of Business Innovation, 2024)
The study aimed to analyse the impact of persuasion on students’ decisions as non-professional investors in the context of the prospect theory. An experimental method involving 576 undergraduate students was used to conduct the research. The experiment manipulated two variables: persuasion and gain/loss, which are elements of the prospect theory. Persuasion was embedded in financial analyst reports, while gain/loss was reflected in the values of companies’ shares and accounting information. The Binomial Test, supplemented by the McNemar test, was used to test the research hypotheses. The main findings of the research were: (i) investors were more likely to choose the company showing gains over the company showing losses; (ii) choices were more frequent for the company whose financial analyst report contained persuasive arguments than for the company without such arguments; (iii) persuasive arguments had a stronger influence than gains and losses when both variables were manipulated together. Therefore, the primary contribution of this work is to highlight that persuasive arguments from a technical authority, in this case the financial analyst, can mitigate the impacts of losses and gains presented in companies’ financial reports.